The Semantics of Yojijukugo Containing the Kanji for 'Tiger' in Yojijukugo no Hakkajiten - Isnaedah Hanum; Ana Natalia (Universitas Cokroaminoto Palopo, 2025)
This study aims to reveal the denotative and connotative meanings of yojijukugo containing the kanji